1999
DOI: 10.2337/diacare.22.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of diabetic gastroparesis.

Abstract: In this relatively large cohort of outpatients with diabetes, there was no evidence that gastroparesis was associated with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
139
2
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(156 citation statements)
references
References 0 publications
7
139
2
8
Order By: Relevance
“…Our study confirms that poor correlation between gastrointestinal symptoms and gastric emptying described in Type 1 diabetic patients [4,27] also exists in Type 2 diabetes. Recent studies have found an association between abdominal bloating and fullness, particularly postprandially [6,36,42] and slow GE, especially when the relationship is assessed according to the severity of symptoms. This study confirms that correlations observed between distinct gastrointestinal symptoms (early satiety/fullness) and GE in Type 1 diabetes [4] may also exist in Type 2 diabetes [6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study confirms that poor correlation between gastrointestinal symptoms and gastric emptying described in Type 1 diabetic patients [4,27] also exists in Type 2 diabetes. Recent studies have found an association between abdominal bloating and fullness, particularly postprandially [6,36,42] and slow GE, especially when the relationship is assessed according to the severity of symptoms. This study confirms that correlations observed between distinct gastrointestinal symptoms (early satiety/fullness) and GE in Type 1 diabetes [4] may also exist in Type 2 diabetes [6] .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the presence of diabetic retinopathy correlates with that of CAN [35] . Both retinopathy and CAN are associated with higher mortality while gastroparesis may not be [7,36,37] . Female gender has been reported previously [13] to be associated with an increased rate of diabetic gastroparesis; this is also the case for delayed gastric emptying in functional dyspepsia [38] .…”
Section: Discussionmentioning
confidence: 99%
“…In this condition there may be emesis of undigested food. Most commonly extreme irregularity and unpredictable fluctuations of the blood glucose [4] due to the erratic absorption of food may appear. In the extreme states the life of the patient is miserable with wasting and loss of weight.…”
Section: Pathophysiology and Symptomsmentioning
confidence: 99%
“…Он существенно снижает качество жизни практический во всех сферах (физической, психоэмоциональной, ментальной, социальной и др.) независимо от наличия других коморбидных факторов, таких как возраст, курение, алкоголь или тип Сд [33,48].…”
unclassified
“…из 62 оставшихся в живых пациентов снижение скорости опорожнения желудка от твердой пищи было зафиксировано у 32 пациентов (52%), от жидкой пищи -у 18 пациентов (29%), а эзофагеальный транзит был нарушен у 17 больных (27%). Среди умерших продолжительность Сд (р = 0,048) и степень тяжести нейропатии (р = 0,046), ретинопатии (р = 0,017) и нарушение эзофагеального транзита (р = 0,017) были достоверно выше, чем у оставшихся в живых пациентов [8,33]. в то же время, другие исследователи (Jung et al) предоставили убедительные доказательства о том, что наличие гастропареза ассоциируется с повышенной заболеваемостью и смертностью, повышением числа госпитализаций, в том числе ургентных, и увеличением объема медицинской помощи [31].…”
unclassified